2010
DOI: 10.1111/j.1439-0310.2009.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Assortative Shoaling in the Guppy (Poecilia reticulata): The Role of Active Choice

Abstract: Many fish species exhibit size‐assortative shoaling, which is often thought to be driven by predation risk. Recent fieldwork has revealed that guppies (Poecilia reticulata) are more size assorted in high‐predation populations than in low‐predation ones. However, size assortment does nonetheless occur in some low‐predation populations, suggesting that predation is unlikely the sole driving force behind size‐assortment. Here, we investigated in the laboratory the potential role of active choice in size‐assortati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
0
20
1
Order By: Relevance
“…A preference for shoaling with large conspecifis over smaller ones has been shown in a number of fish species such as European minnows [61], two-spotted gobies [60], guppies [62] and mosquitofish [63], [64]. Although this behaviour has associated costs, such as increased resource competition, the preference may indicate that benefits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A preference for shoaling with large conspecifis over smaller ones has been shown in a number of fish species such as European minnows [61], two-spotted gobies [60], guppies [62] and mosquitofish [63], [64]. Although this behaviour has associated costs, such as increased resource competition, the preference may indicate that benefits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Living with tilapia for long periods of even 120 days, however, neither helped the climbing perch to develop a preference for heterospecific individuals nor did the subject fish exhibit a bias towards familiar heterospecific over unfamiliar heterospecific or unfamiliar conspecific individuals. Moreover, the lack of significant variation in the frequency of decision-switching¾"the frequent movement that fish display across the available stimulus shoals in order to sample them and make an ultimately beneficial choice" (Jones et al 2010)¾shown by our climbing perch in the various social contexts tested may be taken as an indication of the ambivalence displayed by the subject fish towards conspecific and exotic heterospecific individuals. According to Quattrini et al (2018), individual fish may take a decision to join a shoal of heterospecifics if it experiences relatively fewer phenotypic differences between its own and the other species.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously found that large guppy females prefer to shoal with similar-sized (large) but not smaller conspecifics while small guppy females did not shoal assortatively but also preferred to shoal with larger females [26]. Small individuals can benefit from associating with larger conspecifics if the larger ones take away the attention of harassing males [27, 28] or predators [29].…”
Section: Discussionmentioning
confidence: 99%